Jurnalisme dalam Kerangka Memori Kolektif - Muhammad Aswan Zanynu (Avant Garde, 2017)
This article aims to elaborate the role of journalism as a collective memory agent.The theoretical grounding is derived from the pattern of media relations andreality formulated by McQuail (2010). This literature review presents theoriesand concepts related to journalism, collective memory, and also media memory.The findings suggest that journalistic practice has a close relationship withcollective memory work. When articulated through the mass media, the work ofjournalism is then seen as a media memory phenomenon. As a memory agent, thejournalist's authority and social politic context are two fundamental things in thestudy of media memory. Off from some doubts over the professionalism ofjournalists in exercising their memory authority, prospective memory isrecommended for their run. This will enrich the meaning of the past, the presentday, and the direction that will be directed towards society in the future.